Digital Divide for Persons with Disabilities Related to Indonesian Information Technology Accessibility in Law Perspective - Nurhayati, Siti; Kardi, Kardi (ADLIYA: Jurnal Hukum dan Kemanusiaan, 2024)
Website accessibility and digital content for people with disabilities in Indonesia are still low. According to the Internet Inclusive Index Data, Indonesia ranks 66th out of 120 other countries with a score of 69.75 and does not meet the standards of the Web Content Accessibility Guideline. Although Indonesia has Law Number 8 of 2016 concerning Persons with Disabilities and ratified the United Nations Convention on the Rights of Persons with Disability (UNCRPD) in 2011, the right to information technology accessibility has not been fully fulfilled. This research identifies the factors of the digital divide for people with disabilities and seeks solutions to achieve the concept of inclusive digital. As normative juridical research, a statutory approach is used and analysed in a qualitative descriptive manner. The factors causing the digital divide involve legal substance, institutional structure, and community culture. Inclusive digital can be realised with exemplary implementation of Article 5 and Article 127 of Law Number 8 of 2016. The Ministry of Communication and Information Technology must provide a unique portal as a universal design reference, creating an accessible digital information ecosystem. In the cultural context, there needs to be a shift from the paradigm of compassion to human rights, where people with disabilities have information technology capabilities. Society must also create an inclusive environment in which persons with disabilities are considered equal to non-disabled persons and no longer excluded from their environment.